Reduction of the Chattering Phenomenon By Using Softened Several Ramps Mode Control of an Induction Machine - Z. ZEGHDI; L. BARAZANE; A. LARABI; H.A. MESAI; H. BAKINI (Universty of El-oued جامعة الوادي, 2019)
The principal objective of this paper consists in introducing the sliding mode control concepts in the speed’s regulations control scheme of the induction machine powered by static converters. The control by sliding mode is an interesting technique for solving the problem of robustness of the adjustment with respect to the variation of the load. So, the control law in this technic is expressed mainly from the quantity to be regulated and the number of derivatives. In practical applications, the main disadvantage associated with the command is the phenomenon of chattering. In order to minimize the amplitude of oscillations, we propose a technique of variable structure control which is softened several ramps control. In this context, firstly, we will be introducing some general notions on nonlinear systems as well as the design of sliding mode control. Secondly, they will try to establish a methodology for designing this control (conventional control and softened several ramps control). Each stage of such study is illustrated and validated by simulation results. Finally, we will be conducting robustness testing to evaluate our order.
Intervention
Keywords: Sliding Mode Control; Softened Several Ramps Control; Induction Machine; Phenomenon of chattering.